Pengaruh Faktor-faktor Penilaian E-Government Terhadap Kinerja Website Online Single Submission di Kabupaten Cilacap - Noviaristanti, Siska; Rengganis, Rara Ayu (School of Business, Bogor Agricultural University (SB-IPB), 2023)
This study aims to analyze the factors that impact e-government institution performance. E-government is public services with information and communication technology (ICT) to facilitate citizen administration needed. One form of public service is in the field of licensing. The government created a licensing system called Online Single Submission (OSS). The presence of OSS makes it easier for the citizen because it is flexible to decreasing face-to-face meetings with the State Civil Apparatus (ASN) and could avoid bad things such as corruption, collusion, and nepotism. This study was conducted to determine the OSS performance assessment in Cilacap through availability efficiency, information security, information quality, service functionality, transparency, and trust. Quantitative data was collected by distributing questionnaires to the citizen who applied for permits in January-May 2022, with as many as 321 samples. Data were analyzed using Structural Equation Modeling (SEM) on LISREL 8.8 software. The results all show excellent except for transparency which has good. Therefore this research model could be applied further to measure the performance of e-government. Keywords: e-government, online single submission, performance, structural equation modeling, website